Effects of biuret on sweet sorghum (Sorghum Bicolor L.) (Moench) evaluated by the development of plant - Ferreira, Jorge H.; Mello, Francisco de A.F. de; Crocomo, Otto J. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1986)
This paper relates an experiment carried out at the Departamento de Solos, Geologia e Fertilizantes of the Escola Superior de Agricultura "Luiz de Queiroz" from the Universidade de São Paulo, Brazil, to observe the phytotoxic effects on sweet sorghum (Sorghum bicolor L.) of different doses of biuret added to urea and applied both to soil and leaves. Two types of soils were used-Sands Quartz and Terra Roxa, a clayish soil from the municipality of Piracicaba. The treatments were as fallows: 1. 1.15 g/N pot in soil 2. 1.15 g/N pot + 1% biuret in soil 3. 1.15 g/N pot + 2% biuret in soil 4. 1.15 g/N pot + 3% biuret in soil 5. 1.15 g/N pot, foliar application 6. 1.15 g/N pot + 1% biuret, foliar application 7. 1.15 g/N pot + 2% biuret, foliar application 8. 1.15 g/N pot + 3% biuret, foliar application The amount of urea applied was 2,5 g/pot The results showed that both soil and foliar biuret applications did not affect the plant development, which was evaluated by plant height and leaves and stem dry matter.